Fungal Infection in Co-infected Patients With COVID-19: An Overview of Case Reports/Case Series and Systematic Review - Seyedjavadi, Sima Sadat; Bagheri, Parmida; Nasiri, Mohammad Javad; Razzaghi-Abyaneh, Mehdi; Goudarzi, Mehdi (Frontiers in microbiology, 2022)
Fungal co-infections are frequent in patients with coronavirus disease 2019 (COVID-19) and can affect patient outcomes and hamper therapeutic efforts. Nonetheless, few studies have investigated fungal co-infections in this population. This study was performed to assess the rate of fungal co-infection in patients with COVID-19 as a systematic review. EMBASE, MEDLINE, and Web of Science were searched considering broad-based search criteria associated with COVID-19 and fungal co-infection. We included case reports and case series studies, published in the English language from January 1, 2020 to November 30, 2021, that reported clinical features, diagnosis, and outcomes of fungal co-infection in patients with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Totally, 54 case reports and 17 case series were identified, and 181 patients (132 men, 47 women, and 2 not mentioned) co-infected with COVID-19 and fungal infection enrolled. The frequency of fungal co-infection among patients with COVID-19 was 49.7, 23.2, 19.8, 6.6, and 0.5% in Asia, America, Europe, Africa, and Australia, respectively. Diabetes (59.6%) and hypertension (35.9%) were found as the most considered comorbidities in COVID-19 patients with fungal infections. These patients mainly suffered from fever (40.8%), cough (30.3%), and dyspnea (23.7%). The most frequent findings in the laboratory results of patients and increase in C-reactive protein (CRP) (33.1%) and ferritin (18.2%), and lymphopenia (16%) were reported. The most common etiological agents of fungal infections were Aspergillus spp., Mucor spp., Rhizopus spp., and Candida spp. reported in study patients. The mortality rate was 54.6%, and the rate of discharged patients was 45.3%. Remdesivir and voriconazole were the most commonly used antiviral and antifungal agents for the treatment of patients. The global prevalence of COVID-19-related deaths is 6.6%. Our results showed that 54.6% of COVID-19 patients with fungal co-infections died. Thus, this study indicated that fungal co-infection and COVID-19 could increase mortality. Targeted policies should be considered to address this raised risk in the current pandemic. In addition, fungal infections are sometimes diagnosed late in patients with COVID-19, and the severity of the disease worsens, especially in patients with underlying conditions. Therefore, patients with fungal infections should be screened regularly during the COVID-19 pandemic to prevent the spread of the COVID-19 patients with fungal co-infection.